Cardiac Tissue Engineering Using Stimuli‐Responsive Biomaterials for the Targeted Therapy of Myocardial Infarction - Zarin Tasnim Tisha; Kazi Tasnuva Alam; Tanvir Ahmed (MedComm – Biomaterials and Applications)
ABSTRACT Cardiac tissue engineering presents a viable strategy for the targeted therapy of myocardial infarction (MI), overcoming the limitations of existing therapies in cardiac repair and regeneration. This review explores the potential of stimuli‐responsive biomaterials that engage with the cardiac environment by reacting to various environmental stimuli including pH, temperature, enzymes, ultrasound, and reactive oxygen species. These materials enable precise drug delivery, modulate cellular responses, and enhance tissue regeneration. Biomaterials such as hydrogels, polymers, chitosan, collagen, and alginate improve the accuracy and effectiveness of targeted and localized delivery of drugs, stem cells, and growth factors, thus improving the precision and efficacy of treatments. The review looks at the ability of these biomaterials to mimic the complex biochemical and mechanical cues of a healthy myocardium. The challenges and prospects of clinical applications for stimuli‐responsive biomaterials are discussed, highlighting their transformative potential in targeted cardiac therapy while improving outcomes for patients with MI.